3D Printed Hollow‐Core Terahertz Optical Waveguides with Hyperuniform Disordered Dielectric Reflectors. Issue 12 (14th September 2016) - Ma, Tian; Guerboukha, Hichem; Girard, Martin; Squires, Andrew D.; Lewis, Roger A.; Skorobogatiy, Maksim
Abstract : Novel hollow‐core THz waveguides featuring hyperuniform disordered reflectors are proposed, fabricated, and characterized. The reflector comprises aperiodically positioned dielectric cylinders connected with dielectric bridges. The proposed waveguides are fabricated using a 3D MultiJet printer. Optical properties of the fabricated waveguides are investigated numerically using finite element method, as well as experimentally using terahertz time‐domain spectroscopy. The results confirm that proposed waveguides exhibit sizable photonic bandgaps (21%) even with relatively low refractive index contrast (resin/air). Position of the bandgaps can be easily tuned by varying reflector geometrical parameters. Abstract : Hollow core waveguides featuring hyperuniform disordered reflectors are proposed for applications in the terahertz range. The proposed waveguides are fabricated using a 3D MultiJet printer and characterized by a terahertz time‐domain spectroscopy system. The proposed waveguides exhibit sizable photonic bandgaps (20%) whose positions and widths can easily be tuned by varying reflector geometrical parameters.